Create a controllable self-propelled hydrogel swimmer - Yap, Darren Zhi Han (Nanyang Technological University, 2022)
Hydrogels remain a subject of interest due to their hydrophilic nature that allows for absorption of large volumes of water, non-toxicity, and capability to undergo both swelling and shrinkage to cater for controlled diffusions. When used as a fuel in swimmers, they allow for autonomous propulsions based off the Marangoni effect, which makes them highly useful in potential applications such as wastewater treatments and oil spill cleaning. This study outlines the preparation of triangular PDMS micro-swimmers driven by two different fuels: sodium alginate hydrogel precursor mixed with ethanol and crosslinked alginate hydrogel infused with ethanol. The triangular PDMS swimmers are fabricated with controlled dimensions to ensure they do not break surface tension of the solution, which is paramount for its autonomous propulsion. The swimmers are placed in calcium chloride solution where they swim autonomously and are recorded to analyse their speed and swimming duration for comparison, using a particle tracking program. Our results reveal that the hydrogel precursor-driven swimmers outperform their counterparts during the speed analysis, however there are inconclusive results during the comparison of their swimming durations. Ultimately, with their enormous amenability to customizations which can modify performances based on preferences, these hydrogels serve as promising vehicles for autonomous pollution cleaning.